Perencanan dalam Perspektif Islam (Kajian Tafsir-Hadis Tematik) - Endah Tri Wisuda Ningsih (Institut Ilmu Keislaman Zainul Hasan Genggong, 2016)
In the literature of Management Sciences found a varietyof definitions of the meaning of management. However, the definitionindicates a process that occurs in a management is the definition madeby Ricky W. Griffin which defines management as a process of planning,organizing, coordinating, and controlling resources to achieve thegoals and objectives effectively and efficiently. Referring to the ordermanagement process, then planning is the most early and decisive steptowards the goal of management itself. In our opinion, that the peoplewho are lucky are those who have a good plan in living her life. Thisis the nature of the planning process in which ideals are translated intoaction. Sfesifik-measures designed to achieve realistic goals.